Relative Changes in Krill Abundance Inferred from Antarctic Fur Seal - Huang, Tao (Public Library of Science, 2011)
Antarctic krill Euphausia superba is a predominant species in the Southern Ocean, it is very sensitive to climate change, and it supports large stocks of fishes, seabirds, seals and whales in Antarctic marine ecosystems. Modern krill stocks have been estimated directly by net hauls and acoustic surveys; the historical krill density especially the long-term one in the Southern Ocean, however, is unknown. Here we inferred the relative krill population changes along the West Antarctic Peninsula (WAP) over the 20th century from the trophic level change of Antarctic fur seal Arctocephalus gazella using stable carbon (δ(13)C) and nitrogen (δ(15)N) isotopes of archival seal hairs. Since Antarctic fur seals feed preferentially on krill, the variation of δ(15)N in seal hair indicates a change in the proportion of krill in the seal's diets and thus the krill availability in local seawater. For the past century, enriching fur seal δ(15)N values indicated decreasing krill availability. This is agreement with direct observation for the past ∼30 years and suggests that the recently documented decline in krill populations began in the early parts of the 20th century. This novel method makes it possible to infer past krill population changes from ancient tissues of krill predators.